Editing object behaviour in video sequences - Scholz, V.; El-Abed, S.; Seidel, H. P.; Magnor, M. (Computer Graphics Forum, 2009)
While there are various commercial-strength editing tools available today for still images, object-based manipulation of real-world video footage is still a challenging problem. In this system paper, we present a framework for interactive video editing. Our focus is on footage from a single, conventional video camera. By relying on spatio-temporal editing techniques operating on the video cube, we do not need to recover 3D scene geometry. Our framework is capable of removing and inserting objects, object motion editing, non-rigid object deformations, keyframe interpolation, as well as emulating camera motion. We demonstrate how movie shots with moderate complexity can be persuasively modified during post-processing.